Ancient Egypt, new technology the present and future of computer visualization, virtual reality and other digital humanities in Egyptology - Lucarelli, Rita 1972-; Roberson, Joshua Aaron; Vinson, Steve (Brill, 2023)
"This volume of collected studies takes stock of most recent developments in Egyptology and the Digital Humanities, considering future directions for the application of new technologies in Egyptology. The book presents the results of an international conference held in 2019 at Indiana University - Bloomington, in which Egyptologists and digital humanists with interest in Egyptology gathered in 2019 to present current projects in 3D modeling, virtual and augmented reality, game technology, digital pedagogy, database projects, computational and corpus linguistics and E-publications. Those projects, along with a selection of others that were not presented in Bloomington, are now described and discussed in this volume"
Keywords: Methodologie; Digital Humanities; Visualisierung; Dreidimensionales Bild; Ägypten -- Altertum; Egyptology / Data processing / Congresses; Egyptology / Methodology / Congresses; Digital humanities / Congresses; Three-dimensional imaging in archaeology / Congresses; Information visualization / Congresses; Conference papers and proceedings; Aufsatzsammlung; Konferenzschrift -- Indiana University -- 29.03.2019-31.03.2019 -- Bloomington, Indiana